Physical Composition Of Beef Carcass To Selling Price - Ni Made Ayu Gemuh Rasa Astiti; Komang Nita Wedaningsih; I Kadek Wira Parwata (Pusat Publikasi Nusantara, 2023)
The cattle industry in Indonesia is very important because it can provide an adequate supply of meat for the community. However, the cattle industry in Indonesia still faces various challenges, such as increasing production costs and low productivity. One way to overcome these challenges is to feed cattle with technology. The purpose of this study was to identify the effect of the physical composition of beef carcasses on the selling price of beef fed with technological feed. This study used a qualitative method with a descriptive approach. Data were collected using observation and literature study techniques. The results showed that the physical composition of cattle carcasses affects the selling price of beef. Cattle with heavier carcasses and a higher percentage of meat tend to have a higher selling price. In addition, cattle with a lower percentage of fat also tend to have a higher selling price. These findings suggest that the use of feed technology can improve the physical composition of cattle carcasses and increase the selling value of beef